Bariatric Surgery is Associated With Decreased Progression of Nonalcoholic Fatty Liver Disease to Cirrhosis: A Retrospective Cohort Analysis. Issue 1 (July 2020) - Wirth, Keith M.; Sheka, Adam C.; Kizy, Scott; Irey, Ryan; Benner, Ashley; Sieger, Gretchen; Simon, Gyorgy; Ma, Sisi; Lake, John; Aliferis, Constantin; Leslie, Daniel; Marmor, Schelomo; et al.
Abstract : Objective: This study sought to compare trends in the development of cirrhosis between patients with NAFLD who underwent bariatric surgery and a well-matched group of nonsurgical controls. Summary of Background Data: Patients with NAFLD who undergo bariatric surgery generally have improvements in liver histology. However, the long-term effect of bariatric surgery on clinically relevant liver outcomes has not been investigated. Methods: From a large insurance database, patients with a new NAFLD diagnosis and at least 2 years of continuous enrollment before and after diagnosis were identified. Patients with traditional contraindications to bariatric surgery were excluded. Patients who underwent bariatric surgery were identified and matched 1:2 with patients who did not undergo bariatric surgery based on age, sex, and comorbid conditions. Kaplan-Meier analysis and Cox proportional hazards modeling were used to evaluate differences in progression from NAFLD to cirrhosis. Results: A total of 2942 NAFLD patients who underwent bariatric surgery were identified and matched with 5884 NAFLD patients who did not undergo surgery. Cox proportional hazards modeling found that bariatric surgery was independently associated with a decreased risk of developing cirrhosis (hazard ratio 0.31, 95% confidence interval 0.19–0.52). Male gender was associated with an increased risk of cirrhosis (hazard ratio 2.07, 95% confidence interval 1.31–3.27). Conclusions: Patients with NAFLD who undergo bariatric surgery are at a decreased risk for progression to cirrhosis compared to well-matched controls. Bariatric surgery should be considered as a treatment strategy for otherwise eligible patients with NAFLD. Future bariatric surgery guidelines should include NAFLD as a comorbid indication when determining eligibility. Abstract : Supplemental Digital Content is available in the text